Signs and symptoms in patients with salivary gland hypofunction. Issue 856 (February 1997) - Longman, L. P.; Higham, S. M.; Bucknall, R.; Kaye, S. B.; Edgar, W. M.; Field, E. A.
Abstract : Salivary gland hypofunction can have a devastating effect on oral health and may be an indicator of systemic disease such as Sjögren's syndrome. This prospective study investigates the oral and non-oral signs and symptoms in 120 patients with objective evidence of salivary gland hypofunction (ie, an unstimulated whole salivary flow of < 0.2 ml/min). Patients were questioned about symptoms associated with decreased oral function; non-oral symptoms were also noted. The underlying cause of salivary gland hypofunction was established on the basis of clinical and laboratory findings and further investigations. Eighty-five per cent of patients reported symptoms of decreased oral function in addition to oral dryness. Non-oral signs and symptoms were reported by 106 patients. Fifty-three per cent of patients were diagnosed as having Sjögren's syndrome. The prevalence of the following non-oral signs and symptoms were significantly higher in patients with Sjögren's syndrome, than in those without; a history of dry/irritated eyes, salivary gland swelling, dry skin and reduced lacrimal flow. Salivary gland hypofunction is associated with a wide range of oral and non-oral signs and symptoms. Several of these are of potential value as triggers for the clinician to identify patients with Sjögren's syndrome, and should serve to prompt referral for specialist investigation.